Development of a cornea donation systematic in a São Paulo Cardiology Institution - Martins, Giovanna Parada; Souza, Francival Leite de; Sousa, Andréa Rodrigues de; Bezerra, Karenn Barros (Brazilian Journal of Transplantation, 2010)
Assessment of the cardiovascular risk factors in post-renal transplantation. Cardiovascular disease is the leading cause of mortality in patients with chronic kidney disease (CKD) on dialysis therapy, accounting for about half of every death among those patients. Kidney transplantation is followed by a reduction in the cardiovascular and coronary mortality in the dialysis treatment, but these are also the major cause of death after the first post-transplant year. Purpose: This study aimed to assess changes in traditional markers of risk related to uremia three months after live donor renal transplantation. Methods: Prospective study of 27 patients who underwent by renal transplantation at University Hospital-UFMA from June 2007 to January 2009. The clinical and metabolic data were collected from the first hospitalization day and 3 months after renal transplantation. Results: The mean age was 30.4 years; 57% were men with mean dialysis time of 24 months. After three months of transplantation, there was a significant reduction in systolic BP (128.1 ± 25,7 mmHg to 112.6 ± 15.8 mmHg, p=0.006) and diastolic BP (83.7 ± 19.4 mmHg to 70. 4 ± 10.5 mmHg, p=0.002). Hypocalcemia was observed in 16 patients before transplantation, and in one patient after transplantation (p <0.001). There was a reduction in the serum phosphorus (5.4 ± 1.7 mg/dL to 3.9 ± 1.3 mg/dL, p=0.004), as well as improved levels of hemoglobin and hematocrit in the pre-transplantation (11.2 ± 1.9 g/dL and 34.9 ± 6.0%) as to the post-transplant (12.3 ± 3.4 g/dL and 37.8 ± 6.4%). After three months, there was an increase in the total cholesterol (149.18 ± 35.3 mg/dL to 174.6 ± 44.3 mg/dL, p=0.001), triglycerides (141.8 ± 67.4 mg/dL for 200.1 ± 102.9 mg/dL, p=0.008) and fasting blood glucose (87.55 ± 12.12 mg/dL to 107.44 ± 35.85 going mg/dL, p=0.002). Conclusion: This study demonstrated an early and significant improvement in the amount of risk factors for cardiovascular disease such as anemia, blood pressure and calcium-phosphorus product after renal transplantation. There was a deterioration of the cholesterol, triglycerides and glucose levels in the post-transplant. The monitoring and early treatment of all factors related to the cardiovascular risk among the transplanted population must be performed.